Measurement of jet shapes in top-quark pair events at [Formula: see text] using the ATLAS detector. - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
A measurement of jet shapes in top-quark pair events using 1.8 fb(-1) of [Formula: see text]pp collision data recorded by the ATLAS detector at the LHC is presented. Samples of top-quark pair events are selected in both the single-lepton and dilepton final states. The differential and integrated shapes of the jets initiated by bottom-quarks from the top-quark decays are compared with those of the jets originated by light-quarks from the hadronic W-boson decays [Formula: see text] in the single-lepton channel. The light-quark jets are found to have a narrower distribution of the momentum flow inside the jet area than b-quark jets.